The PROTEIN PHOSPHATASE4 Complex Promotes Transcription and Processing of Primary microRNAs in Arabidopsis. Issue 2 (23rd January 2019) - Wang, Suikang; Quan, Li; Li, Shaofang; You, Chenjiang; Zhang, Yong; Gao, Lei; Zeng, Liping; Liu, Lin; Qi, Yanhua; Mo, Beixin; Chen, Xuemei
Abstract : The highly conserved PROTEIN PHOSPHATASE4 complex coordinates the transcription and processing steps of microRNA biogenesis and plays broader roles in nuclear RNA metabolism in Arabidopsis ( Arabidopsis thaliana ). Abstract: PROTEIN PHOSPHATASE4 (PP4) is a highly conserved Ser/Thr protein phosphatase found in yeast, plants, and animals. The composition and functions of PP4 in plants are poorly understood. Here, we uncovered the complexity of PP4 composition and function in Arabidopsis ( Arabidopsis thaliana ) and identified the composition of one form of PP4 containing the regulatory subunit PP4R3A. We show that PP4R3A, together with one of two redundant catalytic subunit genes, PROTEIN PHOSPHATASE X ( PPX ) 1 and PPX2, promotes the biogenesis of microRNAs (miRNAs). PP4R3A is a chromatin-associated protein that interacts with RNA polymerase II and recruits it to the promoters of miRNA-encoding ( MIR ) genes to promote their transcription. PP4R3A likely also promotes the cotranscriptional processing of miRNA precursors, because it recruits the microprocessor component HYPONASTIC LEAVES1 to MIR genes and to nuclear dicing bodies. Finally, we show that hundreds of introns exhibit splicing defects in pp4r3a mutants. Together, this study reveals roles for Arabidopsis PP4 in transcription and nuclear RNA metabolism.